Object lesson on the influence of Richard Benson - Martin, Lesley A. ca. 20./21. Jh; McGinty, Miko (aperture, 2022)
Through engaging interviews, testimonials, and anecdotes from photographers, curators, printers, and colleagues, Object Lesson: On the Influence of Richard Benson pays homage to a legendary figure whose name is synonymous with the evolving history and philosophy of photographic reproduction. From making platinum prints for Paul Strand and books with Lee Friedlander to his own experiments with inkjet and digital offset processes, and as a teacher and dean of the Yale School of Art, by the time of his death in 2017, Benson had inspired over three decades of students and artisans through his mentorship and work. In words and images, Object Lesson stands as a testament to Benson's wit, wisdom, and incomparable obsession with how photographic images render and connect us to the world
"Text, image, and interview contributions by Michele Abeles, Marion Belanger, Barbara Benson, Richard Benson, Dawoud Bey, Andrew Borowiec, Lois Conner, Matthew Connors, Tim Davis, Benjamin Donaldson, Dru Donovan, Martina Droth, Shannon Ebner, Lucas Foglia, Peter Galassi, John Gambell, Jon Goodman, Bryan Graf, Gail Albert Halaban, Gary Haller, Heyward Hart, Robert J. Hennessey, Peter Kayafas, Lisa Kereszi, Justin Kimball, David La Spina, John Lehr, Susan Lipper, Salvatore Lopes, Peter MacGill, Tanya Marcuse, Lesley A. Martin, Miko McGinty, Sue Medlicott, Sarah Meister, Paul Messier, Andrea Modica, Matthew Monteith, Abelardo Morell, Arthur Ou, Thomas Palmer, Tod Papageorge, Ted Partin, Bradley Peters, John Pilson, Kristine Potter, Caitlin Teal Price, Sergio Purtell, Jock Reynolds, John Robinson, Jeff L. Rosenheim, Sasha Rudensky, Gary Schneider, David Benjamin Sherry, Steve Smith, Mark Steinmetz, Sarah Stolfa, Ka-Man Tse, James Welling, and Jeff Whetstone."--Publisher's website
"An exhibition drawn from this book was shown in Philadelphia at TILT Institute for the Contemporary Image, September 21, 2021-January 8, 2022."--Page 247
Includes bibliographical references
Printed in an edition of 2500 copies
Keywords: Benson, Richard -- 1943-2017; Rezeption; Fotografie; Benson, Richard / 1943-2017 / Influence; Benson, Richard; Photography, Artistic / Philosophy; Influence (Literary, artistic, etc.); Photography, Artistic; Philosophy; Ausstellungskatalog -- TILT Institute for the Contemporary Image -- 21.09.2021-08.01.2022 -- Philadelphia, Pa.